2016
DOI: 10.1128/aac.01323-16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Propranolol Effect on Experimental Acute and Chronic Toxoplasmosis Using Quantitative PCR

Abstract: dCurrent therapies against toxoplasmosis are limited, and drugs have significant side effects and low efficacies. We evaluated the potential anti-Toxoplasma activity of propranolol at a dose of 2 or 3 mg/kg of body weight/day in vivo in the acute and chronic phases. Propranolol as a cell membrane-stabilizing agent is a suitable drug for inhibiting the entrance of Toxoplasma gondii tachyzoites into cells. The acute-phase assay was performed using propranolol, pyrimethamine, and propranolol plus pyrimethamine be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Previously we have shown that the propranolol and ketotifen combined with pyrimethamine was more effective in inhibiting growth of tachyzoites when compared with propranolol and pyrimethamine alone on murine toxoplasmosis [35, 36, 37]. Therefore, further studies should be performed to compare the efficacy of Z. mays and E. caucasicum combination in inhibiting growth of T. gondii.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have shown that the propranolol and ketotifen combined with pyrimethamine was more effective in inhibiting growth of tachyzoites when compared with propranolol and pyrimethamine alone on murine toxoplasmosis [35, 36, 37]. Therefore, further studies should be performed to compare the efficacy of Z. mays and E. caucasicum combination in inhibiting growth of T. gondii.…”
Section: Discussionmentioning
confidence: 99%
“…Spiramycin and metronidazole had synergistic effect in recovery of brain cysts caused by chronic toxoplasmosis. This is due to the influence of metronidazole on increased permeability of the brain to spiramycin; thus, the combination of these two drugs is prescribed to treat cerebral cysts in patients with chronic toxoplasmosis 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, new, less toxic compounds for use against Toxoplasma are critically needed [12, 26]. Natural compounds and traditional herbal medicine have high availability and lower side effects compared with current chemical drugs [16].…”
Section: Discussionmentioning
confidence: 99%